In Vivo Analysis of the 3′ Untranslated Region of GB Virus B after In Vitro Mutagenesis of an Infectious cDNA Clone: Persistent Infection in a Transfected Tamarin - Nam, Jae-Hwan (American Society for Microbiology, 2004)
GB virus B (GBV-B), the virus most closely related to hepatitis C virus (HCV), infects tamarins and causes acute hepatitis. The 3′ untranslated region (UTR) of an infectious GBV-B clone (pGBB) has a proximal short sequence followed by a poly(U) tract and a 3′ terminal sequence. Our investigators previously demonstrated that the 3′ terminal sequence was critical for in vivo infectivity. Here, we tested the effect of deleting the short sequence and/or the poly(U) tract from pGBB; infectivity of each mutant was tested by intrahepatic transfection of two tamarins with transcribed RNA. A mutant lacking both regions was not viable. However, mutants lacking either the short sequence or the poly(U) tract were viable. All four tamarins had a wild-type-like acute infection and developed acute hepatitis. Whereas we found that five tamarins transfected with the wild-type clone pGBB had acute resolving infection, one tamarin transfected with the poly(U) deletion mutant became persistently infected. This animal had viremia and hepatitis until its death at week 90. The genomes recovered at weeks 2, 7, 15, 20, 60, and 90 lacked the poly(U) stretch. Eight amino acid changes were identified at week 90. One change, in the putative p7 protein, was dominant at week 15. Thus, persistence of GBV-B, like persistence of HCV, was associated with the emergence of virus variants. Four tamarins inoculated with serum collected at weeks 2 and 90 from the tamarin with persistent infection had an acute resolving infection. Nonetheless, the demonstration that GBV-B can persist in tamarins strengthens its relevance as a surrogate model for the study of HCV.